Design Of Quality Improvement For Prime Time Program On Zora Radio Using Qfd Method - Hardiyanti Ilmi Aulia; Yati Rohayati; Ika Arum Puspita (eProceedings of Engineering, 2017)
ABSTRACT: PT Radio Karang Tumaritis or mostly known as Zora Radio is a radio in Bandung owned by Yayasan Pendidikan Telkom (YPT). In 2015 Zora Radio changes new segment into young segments. Recorded from the establishment until now, Zora Radio had five times changes their radio segment. The changes that done by Zora Radio made they difficult to earn their revenue target especially from advertisement. That problem caused by the lack of awareness from young people about Zora Radio that has been changes their segment into youth segment. The lack of awareness from young people caused by program that inconsistent in prime time for a weekday program. Therefore, Zora Radio will do a quality improvement for prime time program to achieve their goals. This research aims to provide recommendation to improve Zora Radio based on fifteen true customer needs using Quality Function Deployment Method (QFD). QFD is one of the quality improvement method that focus on Voice of Customer (VoC). In this research, QFD calculation that is used is QFD two iterations, which are House of Quality to determine technical requirement and Part Deployment Matrix to determine critical part. Recommendation formulation drawn up by the data processing and concept selection using decision matrices, analysis and discussion with Management of Zora Radio, as well as benchmark to the competitor that aims to develop prime time program quality of Zora Radio. The recommendation given are, increasing transmitter power, increasing the speed of streaming, expand area of grounding system, eliminate relay program, make a program that consistent on prime time, make a creative team, replace and adding a number of equipment, determining the criteria of announcer age, determining the criteria mastery a foreign language especially English for an announcer, training the announcer on the first time in recruitment stage, evaluation and training periodically for announcer. Keywords: Zora, QFD, True Customer Needs, House of Quality, Part Deployment